Human Resource Practices and Job Satisfaction: A Case Study of Tanzania Public Service College - Balozi, Mohamed Abbasi (2011)
This study explored the influence of HR practices on job satisfaction. In this cross-sectional study, six dimensions of HR practice namely career development, staffing, training and development, performance appraisal, incentives and employee relations were tested against job satisfaction. A total of 100 respondents, both academics and non-academic staffs from Tanzania Public Service College (TPSC) participated in this study. The objectives of this study were answered using correlation and regression analysis, and results are also presented using descriptive statistics. All the six dimensions of HR practices were positively related to job satisfaction, with training and development showing the strongest contribution to job satisfaction. Suggestions are made for further research on ways to increase job satisfaction among the employees.